The economic and social implications of demographic change - Fahey, Tony; FitzGerald, John D.; Maitre, Bertrand (Statistical and Social Inquiry Society of Ireland, 1998)
This Society was founded in the midst of the population crisis caused by the Famine. No crisis on the scale of the Famine occurred again in the Society?s history, but various forms of demographic ?weakness?, such as high emigration, low natural increase and falling population totals, recurred frequently both as facts of life in Ireland and as concerns of the Society. At certain points in the present century, concerns about demographic weakness surfaced elsewhere in Europe, particularly in connection with the widespread fertility decline and the consequent fears of population decline which occurred in a number of European countries between the first and second world wars. More typically, however, Ireland was exceptional for the extent and duration of its population problems, of which its inability to sustain, much less increase, its population numbers was the most fundamental.
Read before the Society, 26 March 1998
Keywords: Demographic change; Fertility; Emigration; Irish demographics; 314.15